2017
DOI: 10.1038/nature25003
|View full text |Cite
|
Sign up to set email alerts
|

KAT2A coupled with the α-KGDH complex acts as a histone H3 succinyltransferase

Abstract: Histone modifications, such as the frequently occurring lysine succinylation1,2, are central to the regulation of chromatin-based processes. However, the mechanism and functional consequences of histone succinylation are unknown. Here we show that the α-ketoglutarate dehydrogenase (α-KGDH) complex is localized in the nucleus in human cell lines and binds to lysine acetyltransferase 2A (KAT2A, also known as GCN5) in the promoter regions of genes. We show that succinyl-coenzyme A (succinyl-CoA) binds to KAT2A. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
349
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 362 publications
(362 citation statements)
references
References 20 publications
10
349
2
1
Order By: Relevance
“…For a long time, the mammalian cellular transferase for lysine succinylation has not been well characterized, while succinylation was regarded as a nonenzymatic modification. Recently, Wang et al showed that histone acetyltransferase KAT2A coupled with α‐ketoglutarate dehydrogenase complex (α‐KGDH) can succinylate nuclear histone H3. However, the succinyl‐transferase in non‐nuclear compartments still remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…For a long time, the mammalian cellular transferase for lysine succinylation has not been well characterized, while succinylation was regarded as a nonenzymatic modification. Recently, Wang et al showed that histone acetyltransferase KAT2A coupled with α‐ketoglutarate dehydrogenase complex (α‐KGDH) can succinylate nuclear histone H3. However, the succinyl‐transferase in non‐nuclear compartments still remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The results show that the pentose phosphate pathway and the endoplasmic reticulum protein processing pathway might be regulated via lysine succinylation of their core enzymes, suggesting a novel tumorigenesis mechanism for breast cancer therapy . Lysine acetyltransferase 2A (KAT2A/GCN5) has been identified as a succinyltransferase that succinylates histone H3 at lysine 79, regulating a series of gene transcriptions and influencing tumor cell proliferation and growth . In gastric cancer, S100A10, which is highly expressed in cancer tissues, was found to be stabilized at lysine residue 47.…”
Section: The Role Of Acylation In Cancer Progressionmentioning
confidence: 99%
“…Cell-free assay, shRNA in cells GCN5 succinylates H3K79 in cell-free assays and shRNA KD of GCN5 or a GCN5 HAT dead mutant reduce H3K79succ in U87 cells, and H3K79succ, H3K9ac and H3K14ac in U251 cells [106] TIP60 H2A-K5, H3K14 H4K5, H4K8 H4K12, H4K16…”
Section: H3k9acmentioning
confidence: 99%